Infectious complications following allogeneic stem cell transplantation by using anti‐thymocyte globulin‐based myeloablative conditioning regimens in children with hemoglobinopathies. Issue 2 (7th March 2015) - Goussetis, E.; Efstathiou, E.; Paisiou, A.; Avgerinou, G.; Zisaki, K.; Giamouris, V.J.; Peristeri, I.; Kitra, V.; Vessalas, G.; Gamaletsou, M.N.; Sipsas, N.V.; Graphakos, S.
Abstract: Background: Anti‐thymocyte globulin (ATG) has been used to prevent graft failure/rejection in the setting of allogeneic stem cell transplantation (allo‐SCT) for hemoglobinopathies; however, epidemiology data for transplant‐related infections in this population are scarce. Method: We retrospectively analyzed the epidemiology of bacterial, fungal, viral, and parasitic infections in a cohort of 105 children and adolescents with β‐thalassemia ( n  = 100) or sickle cell disease ( n  = 5) who underwent allo‐SCT using human leukocyte antigen (HLA)‐identical sibling ( n  = 96) or HLA‐compatible unrelated donors ( n  = 9) in a single institution. All patients received an ATG‐based conditioning regimen. Results: The cumulative incidence of cytomegalovirus (CMV) viremia was 45.7% (95% confidence interval [CI] 33–55%), developing at a median of 48 (range 12–142) days without evidence of overt CMV disease. Herpes zoster developed in 8 patients at a median of 12 months post transplant, while 10 patients presented with late onset hemorrhagic cystitis at a median of 35 days post transplant. The cumulative incidence of bacteremia was 17.1% (95% CI 10.6–25%), occurring at a median of 74 (range 24–110) days. No patient developed probable or definite invasive fungal infection. Four deaths were recorded; 2 of them were attributed to infections (toxoplasmosis and Pneumocystis jirovecii pneumonia, respectively). Conclusion: The rate of infections after allo‐SCT, using an ATG‐containing preparative regimen, in our population of pediatric patients with hemoglobinopathies is comparable to that reported elsewhere with the use of non‐ATG containing regimens.